Does Regular Surveillance Improve the Long-Term Survival of Arteriovenous Fistulas? - Ashwin Shetty; William L. Whittier (International Journal of Nephrology)
The rate of arteriovenous fistula (AVF) placement continues to rise and AVF failure is a major complication. The main cause of AVF failure is stenosis leading to thrombosis. Although the detection of early stenosis with preemptive correction prior to thrombosis seems to be a plausible option to prevent access failure, there is much debate, on the basis of studies of surveillance with arteriovenous grafts, as to whether early surveillance actually improves the longevity of AVFs. Evaluating the available information for surveillance, specifically the data for AVF stenosis and survival, is necessary to determine if surveillance is warranted. These trials have shown that vascular access flow (Qa) surveillance is beneficial in revealing subclinical stenosis. Preemptive angioplasty and surgical revision have shown to decrease thrombosis rates. However, at the present time, there is only limited data on whether preemptive treatment equates to improved long-term AVF survival.